PRINSIP RESTORATIVE JUSTICE PADA DIVERSI DALAM PENEGAKAN HUKUM PIDANA ANAK SEBAGAI PELAKU TINDAK PIDANA - Anshorullah Anshorullah (Jurnal Perspektif Hukum, 2025)
The increase in cases of children in conflict with the law in Indonesia underscores the importance of a more humane approach to law enforcement. This study examines the implementation of the restorative justice principle in diversion practices for children as perpetrators of criminal acts, focusing on the case study of Medan District Court Decision Number 26/Pid.Sus-Anak/2019/PN Mdn. This research uses a normative juridical method with a case study approach to assess the extent to which the principle of diversion is applied to protect children's rights within the criminal justice system. The findings reveal that although Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (UU SPPA) regulates diversion mechanisms, its implementation in the field still faces challenges, particularly regarding coordination among law enforcement officers and public understanding of children’s rights. The decision in this case successfully used diversion as a means of rehabilitation without stigmatizing the child, although there were limitations in resources and social support. This research is expected to encourage better understanding and consistent application of restorative justice principles in handling child cases in Indonesia.